Skull base reconstruction using in situ bone flap in patients with pituitary adenomas treated by endoscopic endonasal approach - Kaile Chen; Kexiang Dai; Zhiyuan Liu; Jinlai Liu; Kuo Yu; Ailin Lu; Peng Zhao (Frontiers in Neurology, 2023)
ObjectiveThe objective of this study is to study the effect of in situ bone flap (ISBF) repositioning, a recently proposed rigid skull base reconstruction technique, on patients diagnosed with pituitary adenoma undergoing endoscopic endonasal approach (EEA).MethodA retrospective analysis was conducted on 188 patients with pituitary adenomas who underwent EEA from February 2018 to September 2022. Patients were divided into the ISBF group and non-ISBF group, according to whether ISBF was used during skull base reconstruction.ResultsOf the 75 patients in the non-ISBF group, 6 had postoperative cerebrospinal fluid (CSF) leakage (8%), while only 1 of 113 patients in the ISBF group (0.8%) had postoperative CSF leakage, indicating that the incidence of postoperative CSF leakage in the ISBF group was significantly lower than that in the non-ISBF group (P = 0.033). In addition, we also found that the postoperative hospitalization days of patients in the ISBF group (5.34 ± 1.24) were significantly less than those in the non-ISBF group (6.83 ± 1.91, P = 0.015).ConclusionISBF repositioning is a safe, effective, and convenient rigid skull base reconstruction method for patients with pituitary adenoma treated by EEA, which can significantly reduce the rate of postoperative CSF leakage and shorten postoperative hospital stays.